تعثر الصكوك: دراسة فقهية تحليلية - عطيات، ضياء الدين محمد يوسف (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2019)
In the last decade, a number of sukuk have defaulted in different countries which has raised questions on the efficiency and Shariah compliance of this financial instrument and whether is it a suitable alternative to conventional bonds. The 2008 global financial crisis has further proved that sukuk is not immune to risks and volatilities. Thus, this study examines the phenomenon of sukuk default, which is one of the challenges facing the sukuk market. Specifically, it studies the nature and causes of sukuk default, types of risks exposures that lead to default, signs, causes and implications of liquidity deficit. The study also establishes the jurisprudential basis for default alongside the Shariah requirements for addressing this problem, bankruptcy of institutions issuing sukuk and lastly suggestions and recommendations that will (God willing) contribute to counter the problems. The study follows an exploratory qualitative method followed by an analysis of five popular sukuk issuances from selected countries, which are considered as noticeable examples for sukuk default. Each sukuk has been presented involving the issuers, types, structures, causes of the default of each and an analysis of the major issues they faced. The study further examines some Shariah and legal issues and how they contribute to default. Lastly, the study presents the major findings and recommendations. It is found that none of the five sukuk structures studied in the thesis is free from structural and Shariah issues as the issuances are not in tangent with the Shariah bearand legal requirements of ownership and its implications. This, as a results, exposes Sukuk holders to essuer's bankrupcy risks and preclude them form recourse to the underlying asset. Indeed, this problem is happening due to the absence of an advanced and standard body that will be responsible for rating and regulating the sukuk market.